2019
DOI: 10.1037/cpb0000147
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the labyrinth of psychological resilience: Establishing criteria for resilience-building programs.

Abstract: There is a growing interest in developing resilience-building programs in the work context. Yet the resilience literature provides no clear answer about what constitutes such a program. The aim of this article is to shed light on this question by presenting a set of criteria for resilience-building programs. We developed these criteria by systematically reviewing studies that synthesized the evidence about the definition, conceptualization, measurement, and enhancement of psychological resilience. A literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 69 publications
0
30
0
3
Order By: Relevance
“…This approach follows previous empirical research studies. 1 A recent overview of a large number of studies and resilience programs further extends the classical definition described here and identifies other strands, which might be especially beneficial for researchers working on the development and implementation of resilience-training (IJntema et al 2019 ).…”
Section: Theoretical Considerationsmentioning
confidence: 82%
“…This approach follows previous empirical research studies. 1 A recent overview of a large number of studies and resilience programs further extends the classical definition described here and identifies other strands, which might be especially beneficial for researchers working on the development and implementation of resilience-training (IJntema et al 2019 ).…”
Section: Theoretical Considerationsmentioning
confidence: 82%
“…The PI-PE model is restricted to psychological resilience, which emphasizes resilience in psychological functioning: the interplay between a person’s behaviour, cognition and affect at a certain time in a certain context (IJntema et al, 2019 ). We derived this model from the existing literature regarding the crucial elements in any process model of psychological resilience (Bonanno et al, 2015 ; Fisher et al, 2019 ; IJntema et al, 2019 ) and from the literature regarding adaptive and maladaptive outcomes following stressful events or circumstances (e.g. Ayed et al, 2019 ; Carver, 1998 ; Zautra, Arewasikporn, & Davis, 2010a ).…”
Section: Psychological Immunity-psychological Elasticity Modelmentioning
confidence: 99%
“…Even though this dichotomy may have an intuitive appeal, scientists nowadays agree that psychological resilience should not be treated as a single, isolated construct (e.g. outcome variable or attribute), but rather as a dynamic process by which people adapt to stressful events or circumstances they are exposed to (Bonanno et al, 2015 ; Fisher et al, 2019 ; IJntema et al, 2019 ). To date, research has identified several trajectories which could be considered as resilience trajectories, for example, sustainability, recovery and (posttraumatic) growth (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological resilience is defined as a dynamic process of positive adaptation in the face of adversity [33,34]. Stressful work-life circumstances increase the risk for poor mental health, yet many people resile despite the difficulties they must endure [35].…”
Section: Introductionmentioning
confidence: 99%